JetValve: Rapid manufacturing of biohybrid scaffolds for biomimetic heart valve replacement. (July 2017) - Capulli, Andrew K.; Emmert, Maximillian Y.; Pasqualini, Francesco S.; Kehl, Debora; Caliskan, Etem; Lind, Johan U.; Sheehy, Sean P.; Park, Sung Jin; Ahn, Seungkuk; Weber, Benedikt; Goss, Josue A.; Hoerstrup, Simon P.; et al.
Abstract: Tissue engineered scaffolds have emerged as a promising solution for heart valve replacement because of their potential for regeneration. However, traditional heart valve tissue engineering has relied on resource-intensive, cell-based manufacturing, which increases cost and hinders clinical translation. To overcome these limitations, in situ tissue engineering approaches aim to develop scaffold materials and manufacturing processes that elicit endogenous tissue remodeling and repair. Yet despite recent advances in synthetic materials manufacturing, there remains a lack of cell-free, automated approaches for rapidly producing biomimetic heart valve scaffolds. Here, we designed a jet spinning process for the rapid and automated fabrication of fibrous heart valve scaffolds. The composition, multiscale architecture, and mechanical properties of the scaffolds were tailored to mimic that of the native leaflet fibrosa and assembled into three dimensional, semilunar valve structures. We demonstrated controlled modulation of these scaffold parameters and show initial biocompatibility and functionality in vitro. Valves were minimally-invasively deployed via transapical access to the pulmonary valve position in an ovine model and shown to be functional for 15 h.